REALITA BUDGET CONSTRAINT DAN TRADE-OFF SEBAGAI KONSEKUENSI BAGI PEMERINTAH DAERAH BALI DALAM PENGIMPLEMENTASIAN KEBIJAKAN DI MASA PANDEMI COVID-19 - Deli Bunga Saravistha; I Made Adi Widnyana; I Wayan Werasmana Sancaya (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The determination of a public policy is of course always faced with the problem of budget constraints which often puts the government in a trade-off situation which is defined as a dilemma condition that makes it difficult to make choices in determining priorities. This is what makes many policies that are not effectively implemented. The neglect of community expectations has resulted in negative reactions ranging from acts of violation even to anarchy that leads to crime. For this reason, it is deemed very important for the government to have a strategy in setting a priority scale so that a policy is more beneficial to people's lives, not just focusing on legal certainty. For this reason, the main problem is related to the efforts of the Regional Government in determining the priority scale so that an implementation of public policy is truly on target.